POFGURST: an expert intelligent system for mechanised oil palm fruit evaluating framework. (2019) - Patkar, Gaurang S.; Anjaneyulu, G.S.G.N.; Mouli, P.V.S.S.R. Chandra
The POFGURST framework is a product bundle for palm oil organic product reviewing initiating unpleasant set based lead models. It is an apparatus for reviewing utilising unthinkable information inside the structure of harsh set hypothesis. POFGURST is intended to support the palm oil reviewing and information revelation process: From beginning perusing and preprocessing of the information, by means of calculation of insignificant trait sets and generation of if-then standards or expressive examples, to approval and investigation of the initiated principles or examples. POFGURST offers an exceedingly natural GUI environment where information navigational capacities are underlined. This product is uniquely intended for oil palm fruit evaluating and also malady expectation.